Connecting Archives and the Classroom - Cook, Sharon Anne (Archivaria, 1997)
This paper explores some components of the debate relating to the professional role of archivists, especially as it has evolved to include or marginalize educational initiatives through public programming. It contrasts the approaches taken by archives and museums to the challenge of public programming in an era of reduced resources. It also considers the changing professional needs of educators as they cope with the demands of an increasingly sophisticated curriculum in a period of mainstreamed classes and reduced budgets. Some of the possibilities for professional partnerships, as demonstrated through the recently-developed educational kit, "Canada's Prime Ministers," will also be suggested. RÉSUMÉ L'article traite de certains aspects du débat entourant le rôle professionnel des archivistes, principalement la façon dont il a évolué pour inclure ou marginaliser les projets éducatifs par l'établissement de programmes publics. Le texte compare les approches retenues par les dépôts d'archives et les musées en matière de programmes publics dans un contexte de restrictions. Il aborde de plus les besoins professionnels changeants des éducateurs qui ont a faire face aux exigences d'un programme d'étude encore plus sophistiqué à une époque d'intégration scolaire et de budgets restreints. On évoque également la possibilité de développer des partenariats professionnels tels que le démontre la création récente de la trousse éducative Les premiers ministres du Canada.